Pendampingan Edukasi: Upaya Peningkatan Peran Orang Tua dalam Meninimalisir Dampak Negatif Pembelajaran Daring pada Anak - Khowim, Imam; Lutfiana Rahmawati, Fina; Guntur H., Bhaswarendra; Fuad U., Mohamad (Ngaliman: Jurnal Pengabdian Kepada Masyarakat, 2022)
The implementation of this mentoring aims to provide education to parents as guardians of students at Kindergarten Pertiwi 1, Joho Pace District, Nganjuk Regency. The assisted activities provided include, (1) compiling booklets as a guide media in assisting children to study at home, (2) holding educational seminars and periodic visits for observation. The results of this dedication show that the process of online learning activities due to the Covid-19 outbreak has had an impact on the inability of effective and efficient learning and there are obstacles experienced by parents in assisting children's learning, such as children finding it difficult to master the material, online learning this is not effective unlike learning at school, children feel bored studying at home, network limitations so that children cannot follow online learning. The role of parents in online learning is that parents always provide assistance to children in the learning process, establishing communication must begin with openness and good intentions, this can create a warm and comfortable atmosphere. Supervision is built on the basis of communication and openness, encouraging or motivating children, directing the child's will. Keywords: education, online learning, the impact of covid-19